How parents' feeding styles, attitudes, and multifactorial aspects are associated with feeding difficulties in children - Evelin Czarny Hasbani; Paula Victória Félix; Patricia Kawai Sauan; Priscila Maximino; Rachel Helena Vieira Machado; Gerson Ferrari; Mauro Fisberg (BMC, 2023)
Abstract Background Parental complaints about feeding difficulties (FD) during childhood are frequent in pediatrics. Behavioral factors about children's feeding and parental aspects are fundamental in solving these problems, but research in this area lacks information considering the joint presence of fathers and mothers. Thus, this study aimed to investigate the features of children, parents and mealtime practices related to FD reported by fathers and mothers and to identify parenting styles, mealtime actions, practices and factors associated with FD in children. Methods 323 parents (226 mothers and 97 fathers) of children aged 1 to 7 years were recruited in the emergency waiting room at Sabará Hospital Infantil, in São Paulo, Brazil, and self-completed electronic questionnaires on parenting style (Caregiver's Feeding Styles Questionnaire), parents' mealtime actions (Parent Mealtime Action Scale), socioeconomic information, personal and children's health data and routine meal practices. Results The prevalence of FD in children was 26.6%. Indulgent parenting style was the most frequent (44.2%), followed by authoritarian (25.1%), authoritative (23.8%), and uninvolved (6.9%) styles. Most parents (75.8%) reported presence during meals, and 83.6% used distractions. Regression analyses after adjustments showed, as factors associated with FD, female children (OR: 2.06; 95%CI: 1.19-3.58), parents' FD history (OR: 3.16; 95%CI: 1.77-5.64), and greater frequency of parents' behavior of offering many food options (OR: 2.69; 95%CI: 1.18-6.14). Parents with indulgent styles had decreased chances of reporting FD in their children (OR: 0.13; 95%CI: 0.06-0.27). Furthermore, the practice of children sharing the family menu (OR: 0.43; 95%CI: 0.18-0.99) and higher frequency of parents' behavior of setting snack limits (OR: 0.44; 95%CI: 0.23-0.85) were inversely associated with FD. Conclusions This study reinforces the multifactorial aspects involved in the feeding difficulties context. It points out the importance of expanding knowledge of the individual role of fathers and mothers to compose a scenario that can guide future studies and interventions. Trial registration CAAE #99221318.1.0000.5567 with registration number 2,961,598.